Estudio de los niveles plasmáticos de homocisteína, ácido fólico y vitamina B-12 en una población limeña de jóvenes adultos - SOBERÓN, MERCEDES (2004)
Objective: To describe the distribution of plasma homocysteine, folic acid, B-12 vitamin concentrations among students living in the city of Lima, Peru. Material and Methods: Transversal cohort study of 65 young adults between 18 and 30 year-old. The plasma homocysteine concentration was determined by fluorescence polarization inmunoassay FPIA from Abbott Laboratories, folic acid by ionic capture and vitamin B-12 by enzimatic assay. Results: The distribution of homocysteine values ranged from 1,40 to 24,04 mmol /L; geometric mean homocysteine 8,32±5,46, median 7,76 mmol/L. Homocysteine geometric means were significantly higher (p=0,005) in men (9,97±4,81 mmol/L) than in women (7,35±2,03 mmol/L). Plasma homocysteine level was significantly correlated with folic acid plasma level (r=-0,329, p=0,007) but not with B-12 vitamin. However, plasma homocysteine level was correlated with body mass index (r=0,391; p=0,001). Conclusions: The distribution of homocysteine levels in our sample is within the reference range already reported. However, there was a complete shift of the homocysteine distribution curve towards lower values. Plasma folic acid levels may be a determinant factor in the variation of homocysteine levels.